Lacanian ink 3 - Ayerza, Josefina, (Lacanian ink, 1991)
Fetishes — Fetish, por Roger Wartel -- Telacan: Tiananmen, por Catherine Liu -- Unconscious Transmission: The Generation "Gap", por Elizabeth Geblesco -- The Ethics of Hysteria & of Psychoanalysis, por Vicente Palomera -- 3 Poems, por Quincy Troupe -- Entrevistas com René Ricard, Silvia Kolbowski e Jonathan Lasker, por Josefina Ayerza.